Techniques to determine the magnitude and direction error of GPS system - Toloza, Juan Manuel (2012)
The Global Positioning System (GPS) allows locating an object in any part of the World with a certain degree of accuracy. Some precision activities need to operate with a sub-metric accuracy [1]. In this article, techniques are introduced to determine the magnitude and direction error of GPS system. With this error vector it is possible to correct any low cost standard GPS receiver to improve the positional accuracy.